Harmful algal bloom of dinoflagellate Blixaea quinquecornis in Peru - Romero, Liz (2022)
In the present work, harmful algal blooms of the dinoflagellate Blixaea quinquecornis (Abé) Gottschling, 2017 are recorded for the first time for coastal waters of the Peruvian sea. The taxonomic determination of this species was done with light microscopy, Scanning Electron Microscopy (SEM), and Differential Interference Contrast (DIC) microscopy. The thecal formula is: pp, 3’, 2a, 7’’, 5c, 5”’ and 2’’’ 4s. Blixaea quinquecornis was recorder in Sechura, Miraflores and Paracas bays between 2014 – 2016, mainly with algal blooms of 3.2 x105 cel.L-1 (Miraflores) and 2.11x105 cel.L-1 (Paracas) and 4.11 x104 cel.L-1 (Paracas) in autumn of 2016. Blixaea quinquecornis was found alternating with algal bloom produced by the athecate dinoflagellate Akashiwo sanguinea. The physicochemical variables associated with the bloom of B. quinquecornis were SST (18.5 to 26.6° C), salinities (34.7 to 35.325), pH (7.32 to 12.5), and dissolved oxygen (3.8 to 12.5 mL/L). The bloom of B. quinquecornis in Miraflores Bay was positively associated with the increase in SST, salinity and negatively with the concentration of nitrates, whereas the algal blooms of A. sanguinea were positively correlated with the concentration of phosphates and oxygen. The record of the bloom of B. quinquecornis in the 3 bays coincided with unusual sea warming event associated with the El Niño phenomenon 2015-2016.